Comparison of Bus Driving Control Based on Working Shift Hour and Impact on Bus Fuel Consumption - M. M., Rohani; B. D., Daniel; M.Y., Aman; J., Prasetijo; R., Buhari; N. N., Mohd Nawi; N. S. A., Sukor; S. A., Hasan (EDP Sciences, 2017)
This study is aimed to investigate and compare how the work schedule of bus drivers in urban areas can have impact on bus drivers' control on speed and acceleration. This study also assesses the influence of bus driving behavior on fuel consumption. The work schedule assessed in this research is morning shift (6.00 am to 3.00 pm), afternoon shift (3.00 pm to midnight) and direct shift (6.00 am to midnight). The result from this study indicated that for all driving shifts, drivers spent more than 70% of their driving time for accelerating and braking. Drivers were also significantly driving faster and applying sharper acceleration when accelerating and braking during morning shift. The variation of bus driving behavior between different working shift hours were found to influence bus fuel consumption significantly.